PELATIHAN DAN IMPLEMENTASI BUDIDAYA MAGGOT BSF: SOLUSI PENANGANAN SAMPAH ORGANIK UNTUK PEMENUHAN KEBUTUHAN PANGAN TERNAK DAN IKAN AIR TAWAR - Dewi Susilowati (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2023)
The problem of waste, especially organic waste, requires serious handling because of the negative impact on the health of the environment and the surrounding community. The solution for dealing with organic waste can use organic waste bioconversion technology using the Black Soldier Fly (BSF) maggot. The BSF life cycle is as follows: egg, baby larva, grower phase, adult maggot, prepupa, pupa, and adult fly. Organic waste is eaten by the grower phase, which will become an adult maggot ready for harvest within two weeks. The products produced at this stage are mature maggots, food waste (kasgot), or organic fertilizer. Adult maggots can be used as feed ingredients for fish or chicken livestock, while women farmer groups can use castor or organic fertilizers to fertilize vegetable crops. Waste bank groups and youth organizations can earn income from the contributions of residents who receive garbage collection services from door to door. The benefits for the entire Menganti village community are ensuring a clean and healthy environment